Endogenous and Exogenous Vanilloids Evoke Disparate TRPV1 Activation to Produce Distinct Neuronal Responses - Kumar, Rakesh; Geron, Matan; Hazan, Adina; Priel, Avi (Frontiers in Pharmacology, 2020)
Neuronal signals are processed along the nociceptive pathway to convey discriminative information, which would manifest in the produced pain sensation. The transient receptor potential vanilloid 1 (TRPV1), an important signaling complex in nociceptors termini, is activated by different noxious stimuli that underlie distinct pain sensations. For example, while endovanilloids are associated with inflammatory pain and hypersensitivity through TRPV1 activation, the exovanilloid toxin, capsaicin, evokes an acute pain by activating this channel. Differences in the TRPV1 activation profile evoked by exogenous and endogenous vanilloids were suggested to underlie this disparity in pain sensations. However, the cellular processes that lead to these differences in pain sensation mediated by the same channel are not fully understood. Here, we sought to describe the neuronal response of TRPV1-expressing nociceptors to exo-and endovanilloids. To this end, we performed current-clamp recordings in rat trigeminal neurons exposed to either capsaicin or intracellular endovanilloids produced downstream of the bradykinin receptor BK2. Our results show that lipoxygenase metabolites generate persistent TRPV1-dependent action potential firing while capsaicin evokes robust depolarization and high-frequency firing that is quickly terminated by depolarization block. Additionally, we found that a weak TRPV1 activation prolongs action potential firing. Overall, our results indicate different firing patterns evoked by inflammatory mediators and capsaicin via TRPV1 that correlate with the respective subsequent pain sensation. These findings also suggest that differences in neuronal activation stem from the variable degree of TRPV1 activation they produce.